2009
DOI: 10.1080/00223890903230899
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the MMPI–2 Trauma Profile in Treatment-Seeking Peacekeepers

Abstract: Most available research on MMPI-2 (Butcher, Dahlstrom, Graham, Tellegen, & Kaemmer, 1989) scores in combat veterans suffering from posttraumatic stress disorder (PTSD) has focused on Vietnam veterans. No data are available from peacekeepers suffering from PTSD. The aim of this study was to investigate the relationship between PTSD and the MMPI-2 in a sample of 120 treatment seeking peacekeeping veterans. Results show that relative to a non-PTSD reference group, veterans who screened positive for PTSD scored hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…In the military, after the aforementioned studies on Post Deployment Syndrome and fatigue in Cambodia veterans (De Vries et al, 2000) the Department of Defense also facilitated biological studies in PTSD in alliance with several academic partners to validate the disorder and stimulate research on the disorder. This started with cross-sectional biological studies and later with prospective studies in soldiers, resulting in a flurry of studies that validated what was known and extended the findings because of the use of new designs: Hypothalamus-Pituitary-Adrenal-axis studies (De Kloet et al, 2006) neuroimaging and pain studies (Geuze et al, 2007, 2008), personality (Rademaker, Kleber, Meijer, & Vermetten, 2009), and sleep (Van Liempt et al, 2013). The start of the participation to International Security Assistane Forces deployment was an opportunity to conduct true prospective studies that allowed identification of candidate biomarkers and differentiation of posttraumatic stress, depression, and fatigue (Van Zuiden et al, 2011, 2012), as well as an insight into central brain circuits after deployment (Van Wingen, Geuze, Vermetten, & Fernandez, 2012).…”
Section: Dutch Psychotraumatology Todaymentioning
confidence: 99%
“…In the military, after the aforementioned studies on Post Deployment Syndrome and fatigue in Cambodia veterans (De Vries et al, 2000) the Department of Defense also facilitated biological studies in PTSD in alliance with several academic partners to validate the disorder and stimulate research on the disorder. This started with cross-sectional biological studies and later with prospective studies in soldiers, resulting in a flurry of studies that validated what was known and extended the findings because of the use of new designs: Hypothalamus-Pituitary-Adrenal-axis studies (De Kloet et al, 2006) neuroimaging and pain studies (Geuze et al, 2007, 2008), personality (Rademaker, Kleber, Meijer, & Vermetten, 2009), and sleep (Van Liempt et al, 2013). The start of the participation to International Security Assistane Forces deployment was an opportunity to conduct true prospective studies that allowed identification of candidate biomarkers and differentiation of posttraumatic stress, depression, and fatigue (Van Zuiden et al, 2011, 2012), as well as an insight into central brain circuits after deployment (Van Wingen, Geuze, Vermetten, & Fernandez, 2012).…”
Section: Dutch Psychotraumatology Todaymentioning
confidence: 99%
“…Control subjects 0.7 ± 0.0 (0-3) IV Bakke et al [3] In addition, the NOT-S protocol has also been used to assess treatment outcomes of surgery in children with adenotonsillar hypertrophy [6]. To date, results concerning ratings of quality-of-life [10,11], personality traits [12] and NOT-S data [4,13] have been illustrated using diagrams or profiles with connected plots. Such presentations may be useful to facilitate the understanding of results and for the comparison of data between studies.…”
Section: Introductionmentioning
confidence: 99%
“…Higher scores on the HY scale may be reflect concentration problems, somatic complaints, helplessness, and anger control problems of PTSD 47,48). Previous studies reported that SC scale of the MMPI-2 was important for the diagnosis of PTSD 25,26). SC scale can be reflect the problem of self-integration after trauma experience.…”
Section: Discussionmentioning
confidence: 97%
“…Related studies have suggested that the depression (D), psychasthenia (PT), and schizophrenia (SC) scales of the MMPI-2 are important for the diagnosis of PTSD 25,26,27). Some studies have focused on the D-SC and PT-SC code types 28,29,30,31).…”
Section: Introductionmentioning
confidence: 99%